Privacy paradox dynamics and continuance intention in telemedicine use: Trust as a mediator with perceived benefits and digital health literacy as moderators - Dody Mulyanto; Sri Wulandari; Agus Susanto; Samer Ali Al-Shami (Jurnal Manajemen dan Pemasaran Jasa, 2026)
This study examines users’ intention to continue using telemedicine through the privacy paradox perspective by positioning trust as an intervening mechanism and by considering perceived benefits and digital health literacy as conditional factors. A quantitative explanatory survey was conducted with 455 telemedicine users from multiple platforms in Central Java, Indonesia. The proposed relationships were assessed using PLS-SEM to evaluate direct effects, mediation, and moderation. The findings reveal that privacy concern reduces both trust and continuance intention. Trust, in turn, enhances continuance intention and partially explains the relationship between privacy concern and continued use. Perceived benefits and digital health literacy also increase continuance intention. The moderation analysis shows that perceived benefits strengthen the effect of trust on continuance intention, whereas digital health literacy weakens the negative influence of privacy concern on continued use. These findings demonstrate that users may continue using telemedicine despite privacy concerns when they trust the platform, perceive strong service benefits, and have sufficient digital health literacy. This study contributes to telemedicine continuance literature by integrating privacy concern, trust, perceived benefits, and digital health literacy into a conditional mediation model. The findings also offer practical implications for telemedicine providers to improve transparency, data protection, service value, and user literacy. Future research should employ longitudinal and cross-regional designs to improve generalizability.